“It Is My Responsibility to Escort My Child to School …” Factors Influencing Parental Involvement in Educating Children with Disabilities in Malawi - David John Musendo; Maria Zuurmond; Thomas Andrea Nkhonjera; Sarah Polack; Daksha Patel (Social Sciences, 2024)
This study aimed to explore the factors that influence parental involvement in supporting the education of children with disabilities in Malawi, thereby generating insights into the barriers and facilitators they face. We conducted focus groups and in-depth interviews with 25 participants from Nkhata Bay District: teachers, parents, and children with disabilities. We used the COM-B model to analyse how parents’ capabilities, opportunities, and behaviours influence their involvement in their children’s education. This study revealed that parents of children with disabilities showed willingness, optimism regarding their children’s future, and a strong sense of responsibility for their education. However, factors such as the limited knowledge of children’s learning needs, time, low confidence, and financial challenges have constrained their involvement. Schools and communities frequently limit participation opportunities by not consistently practising or championing parental involvement in policies and actions. This study sheds light on the complex interplay between knowledge, practical constraints, and external support systems that shape parental involvement in the education of children with disabilities. Further research aimed at creating tailored and context-relevant interventions to improve parental involvement in the education of children with disabilities in low-income settings is required.